ANALISIS VALIDASI KUALITAS SOAL TES HASIL BELAJAR PADA PELAKSANAAN PROGRAM PEMBELAJARAN - Sudji Munadi (Jurnal Cakrawala Pendidikan, 2011)
Abstract: An Analysis of the Validation of the Quality Achievement Tests in the Learning Program Implementation. This study aims to investigate the test types developed by FE YSU, the steps of the development and validation, and the quality based on theories. This study was a survey involving 192 lecturers who taught basic science and technology subjects in the odd semester of 2008/2009. The sample, consisting of 92 lecturers, was selected using the proportional random sampling technique. The data were collected through documents and questionnaires and analyzed using the descriptive quantitative technique. The results showed that 1) 55.42% of the lecturers developed essays tests for measuring learning achievement, 13.03% developed objective tests, and 31.55% combined both; 2) in the test development process, 35.87% made the test blue-prints and 23.92% did not; only 13.59% developed new tests, 2.74% used old tests, and 46.19% combined the old tests with the new ones; 3) 54.89% rechecked the tests and 3.73% did not, 25.50% rechecked the tests by themselves and 17.85% rechecked the tests with group members of the same subject, 2.18% had other lecturers fully check the tests, 32.85% rechecked the essay tests, 11.18% rechecked the objective tests, and 91% rechecked mostly the relevance between the test and the learning competence; and 4) theoretically, 87% of the tests developed by lecturers were good in terms of the essence of the test quality. However, there were still some weaknesses in the clarity or the function of pictures and the scoring procedure of each test item (in essay test) and the homogenity of the option length (in objective tests). Keywords: achievement test, test quality, validation